2007
DOI: 10.1021/jo071145s
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic, Crystallographic, Computational, and Biological Studies of 1,4-Difluorobenzo[c]phenanthrene and Its Metabolites

Abstract: 1,4-Difluorobenzo[c]phenanthrene (1,4-DFBcPh) and its putative metabolites, the dihydrodiol and diol epoxides, have been synthesized and structurally characterized, and the extent of DNA binding by the metabolites has been assessed. 1,4-DFBcPh and 1,4-difluoro-10-methoxybenzo[c]phenanthrene were prepared by photochemical cyclization of appropriate naphthylphenylethylenes. The dihydrodiol was synthesized from 1,4-difluoro-10-methoxybenzo[c]phenanthrene, and the diol epoxides were diastereoselectively synthesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…To date, various methods have been used for the introduction of fluorine into polycyclic aromatic systems, such as diazotization-fluorination, 11 direct electrophilic substitution, 12 bromine-fluorine exchange, 13 and cyclizations of smaller fluorinated building blocks. 14 Photocyclizations of stilbene like derivatives with appropriate fluorine atom-substituted and often commercially available aryl moieties are known, 10,15 and recently photodehydrofluorination approach to polyfluorinated polycyclic aromatic hydrocarbons has been reported. 15e Although stilbene can be cyclized readily to phenanthrene, it has been reported that α-fluorostilbene could not be cyclized to the fluoro analogue.…”
Section: Introductionmentioning
confidence: 99%
“…To date, various methods have been used for the introduction of fluorine into polycyclic aromatic systems, such as diazotization-fluorination, 11 direct electrophilic substitution, 12 bromine-fluorine exchange, 13 and cyclizations of smaller fluorinated building blocks. 14 Photocyclizations of stilbene like derivatives with appropriate fluorine atom-substituted and often commercially available aryl moieties are known, 10,15 and recently photodehydrofluorination approach to polyfluorinated polycyclic aromatic hydrocarbons has been reported. 15e Although stilbene can be cyclized readily to phenanthrene, it has been reported that α-fluorostilbene could not be cyclized to the fluoro analogue.…”
Section: Introductionmentioning
confidence: 99%
“…Both quinones showed characteristic fjord-region quinonoid proton resonances (d, J = 10.5 Hz), which corresponded well with other quinones of B c Ph and its derivatives. 32e,33,34 …”
Section: Resultsmentioning
confidence: 99%
“…This difference between the two hydrocarbons is likely due to the extreme out-of-plane distortion of DFB c Ph. 34 The series 1 diol epoxide of benzo[ ghi ]fluoranthene (B[ ghi ]F), a compound that is expected to be more planar than both B c Ph and DFB c Ph, surprisingly, also shows a much smaller coupling constant between its carbinol protons ( J = 2.1 Hz), 49 identical to that observed with DFB c Ph. By contrast, the hydroxyl group conformation in the series 1 diol epoxides of both 5-MB c Ph [(±)- 26 )] and H 2 B[ l ]A [(±)- 27 )] are comparable to that in B c Ph.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Huh reported a successful method for the ozonolysis of phenanthrene adsorbed on powdered polyethylene, that can be applied for a large-scale preparation of ozonides [28]. Bae et al [29] explored the impact of the genetic material 1,4-difluorobenzo[c]phenanthrene (1,4-DFBcPh) on the DNA and its distortions. This study has covered the crystallographic, computational, and biological investigations of the compound.…”
Section: Introductionmentioning
confidence: 99%